ANALYSIS OF GENDER ANTHROPOLOGICAL STUDY ON WOMEN'S INVOLVEMENT IN POLITICS - Istiqomah Nur Rahmawati (Adisam Publisher, 2025)
This research analyzes existing literature regarding women's involvement in politics from a gender anthropology perspective. This study aims to understand the dynamics, obstacles and progress faced by women in carrying out political roles in various social and cultural contexts. Using a qualitative approach, this research examines findings from various sources such as books, journal articles and previous research reports. The analysis shows that women still face significant structural inequalities in politics, which are exacerbated by traditional gender norms and systemic discrimination. However, affirmative policy initiatives such as gender quotas have seen an increase in women's representation in legislative councils. Additionally, the importance of social networks, mentorship, and political education are recognized as key factors that can increase women's participation in politics. In the digital era, information technology offers new opportunities for women's political participation, although challenges such as online harassment are also a serious concern. In conclusion, this research confirms that increasing women's involvement in politics requires a holistic and collaborative approach. Change must occur at structural, social and individual levels, supported by just and sustainable policies. In this way, a more inclusive and representative political future can be realized.